2014
DOI: 10.1063/1.4903533
|View full text |Cite
|
Sign up to set email alerts
|

Effective reduction of trap density at the Y2O3/Ge interface by rigorous high-temperature oxygen annealing

Abstract: The impact of thermal post deposition annealing in oxygen at different temperatures on the Ge/Y2O3 interface is investigated using metal oxide semiconductor capacitors, where the yttrium oxide was grown by atomic layer deposition from tris(methylcyclopentadienyl)yttrium and H2O precursors on n-type (100)-Ge substrates. By performing in-situ X-ray photoelectron spectroscopy, the growth of GeO during the first cycles of ALD was proven and interface trap densities just below 1 × 1011 eV−1 cm−2 were achieved by ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…This indicates that the interfacial layer formed through IOF and OPA was mostly the YGeO x layer with the minimal involvement of the GeO 2 formation, which is different from the previous report. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the interfacial layer formed through IOF and OPA was mostly the YGeO x layer with the minimal involvement of the GeO 2 formation, which is different from the previous report. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the good interface quality was most likely driven by the growth of interfacial GeO 2 and thermally stabilizing yttrium germanate. [127] Er-doped GaAs showed resistance switching between the low and high resistance states with voltage sweeping, and the resistance ratio between the two states was more than 1000 times, which is preferable for non-volatile memory operation. [132] The new precursor has also been used to produce to produce Y-doped HfO 2 films with various Y/(Y+Hf) compositions ranging from ca.…”
Section: Other Organolanthanide-catalyzed Reactionsmentioning
confidence: 98%
“…Moreover, the so-called "valency passivation" could effectively suppress the dangling bonds in the interface and consequently improve the interface quality by considering the trivalent nature of Y [8]. Therefore, Y 2 O 3 , which has high k value (12)(13)(14)(15)(16)(17) [6,9] and large bandgap (~5.5 eV) [6,9] is considered to be one of the most promising IPLs for Ge MOS devices. However, the crystallization of Y 2 O 3 is still an issue because of its low crystalline temperature (400°C) [10], which generates a large amount of defects in the film and causes the increase of leakage current [11].…”
Section: Introductionmentioning
confidence: 99%
“…N incorporation into Y 2 O 3 has been suggested to increase the crystalline temperature [11]. Moreover, the barrier effect introduced by N could effectively suppress the diffusion of Ge and O to prevent the formation of GeO x , and further improve the interface quality [12]. In this paper, we further investigate the effect of dielectric (denoted as control sample) was also deposited using the same sputtering conditions as above.…”
Section: Introductionmentioning
confidence: 99%